Farewell, my queen [videorecording (DVD)] - Thomas, Chantal, 1945-; Jacquot, Benoît, 1947-; Ledoyen, Virginie, 1976-; Kruger, Diane, 1976-; Seydoux, Léa, 1985-; Beauvois, Xavier; Lvovsky, Noémie, 1964- (Cohen Media Group : Distributed by Entertainment One, 2013)
Sidonie, who serves as reader to Marie Antoinette and displays a singular romantic devotion to the queen, witnesses the final days of the French Revolution from inside the walls of the Palace of Versailles. The film is seen from Sidonie's point of view, and the story takes place over the course of four days.